2017
DOI: 10.1021/jacs.7b04457
|View full text |Cite
|
Sign up to set email alerts
|

CF2H, a Hydrogen Bond Donor

Abstract: The CFH group, a potential surrogate for the OH group, can act as an unusual hydrogen bond donor, as confirmed by crystallographic, spectroscopic, and computational methods. Here, we demonstrate the bioisosterism of the OH and CFH groups and the important roles of CF-H···O hydrogen bonds in influencing intermolecular interactions and conformational preferences. Experimental evidence, corroborated by theory, reveals the distinctive nature of CFH hydrogen bonding interactions relative to their normal OH hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
188
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(192 citation statements)
references
References 54 publications
4
188
0
Order By: Relevance
“…[13] Finally, Lippard has shown that compounds such as o-nitro-α,α-difluorotoluene can form hydrogen-bonded dimers in solution and the solid-state, similar in shape to o-nitrophenol. [14] The inductive electronwithdrawing effect of the CF 2 H group is similar to that of an OH group [as measured by their σ I values of 0.29 (CF 2 H) and 0. 33 (OH)].…”
Section: Properties Of αα-Difluoroketonesmentioning
confidence: 94%
See 1 more Smart Citation
“…[13] Finally, Lippard has shown that compounds such as o-nitro-α,α-difluorotoluene can form hydrogen-bonded dimers in solution and the solid-state, similar in shape to o-nitrophenol. [14] The inductive electronwithdrawing effect of the CF 2 H group is similar to that of an OH group [as measured by their σ I values of 0.29 (CF 2 H) and 0. 33 (OH)].…”
Section: Properties Of αα-Difluoroketonesmentioning
confidence: 94%
“…In compound 4 a short C–H–O contact between a CF 2 H and an amide is used to stabilise a short peptide mimic into a β‐turn like conformation, overcoming the natural conformational preference to place a fluorine and an adjacent carbonyl group trans ‐coplanar to each other to minimize dipole repulsions . Finally, Lippard has shown that compounds such as o ‐nitro‐α,α‐difluorotoluene can form hydrogen‐bonded dimers in solution and the solid‐state, similar in shape to o ‐nitrophenol . The inductive electron‐withdrawing effect of the CF 2 H group is similar to that of an OH group [as measured by their σ I values of 0.29 (CF 2 H) and 0.33 (OH)].…”
Section: Properties Of αα‐Difluoroketonesmentioning
confidence: 99%
“…[18] To date,n os uccessful example of difluoromethylation of Grignard reagents with BrCF 2 Hh as been described. In view of the important applications of difluoromethyalted arenes in medicinal chemistry, [19] this method would have potential applications in drug discovery and development. In view of the important applications of difluoromethyalted arenes in medicinal chemistry, [19] this method would have potential applications in drug discovery and development.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[b] Determined by 19 FNMR spectroscopy using fluorobenzene as an internals tandard. [b] Determined by 19 FNMR spectroscopy using fluorobenzene as an internals tandard.…”
mentioning
confidence: 99%
“…Organofluorine chemistry has become av ery important field of research over the last decade.I ndeed, the properties of the fluorine atom [1] have at remendous impact on the physicochemical properties of molecules and thus on their bioactivity.T he presence of either af luorine atom or af luorinated group on am olecule can affect the metabolic profile,the lipophilicity,aswell as the binding affinity toward biological receptors.H ence,t he systematic introduction of either the fluorine atom or fluorinated groups to amolecule is avery popular strategy in drug discovery, [2] and the quest for the development of versatile fluorinated bioisosteres is an attractive research area for organic chemists. [3] As part of this field, the CF 2 Hr esidue is considered to be an excellent bioisostere of alcohol and thiol, for instance.Q uite recently, the groups of Saphier [4] and Lippard [5] independently demonstrated the ability of this motif to act as alipophilic hydrogenbond donor.…”
mentioning
confidence: 99%